Experimental study of a solar desalinator driven by thermal oil circuit - JoÃo Vitor Goes Pinheiro (2014)
A solar desalination system basically has two components: the heating unit (solar collectors) and the desalination unit (tower). Among its main advantages, this device does not need electrical power to operate, since it is driven by thermosiphon. In its operation, brackish water is heated and it evaporates. The evaporated vapor rises and hits the coller walls of the above tray, where it condensates and drains through a specially designed geometry, structure to be finally by in a set of gutter. The already demineralized water flows through a main channel where it is stored in a container, outside the desalination tower. The resulting water from this process is pure and free from contamination, either microorganisms or salt. This study analyzes the performance of a desalination system with a desalination tower and a set of three solar collectors. The heat transfer medium between the collector and the tower was thermal oil flow, Lubrax Utile OT-100. The experimental results demonstrate the operation of this type of desalinator, since ideal conditions for its correct functioning was only achieved after the installation of a positive displacement pump, which that promoted the oil circulation. Thermocouples installed in the stages of tower registered the temperature increase throughout the day. Peaks of 77 ÂC were measured in the storage tank of the tower. The mean values of production per day were 25 liters of desalinated water with an average conductivity always less than 10 μS / cm Â, representing a salt removal efficiency greater than 99%. In performance calculation, the best result was obtained when the pumping system was combined with the use of a solar reflector, achieving GOR value of 2.85.